Probiotic supplements and bone health in postmenopausal women: a meta-analysis of randomised controlled trials - Yu, Jiawei; Cao, Gaoyang; Yuan, Shuohui; Luo, Cong; Yu, Jiafeng; Cai, Ming (BMJ open, 2021)
ObjectiveOsteoporosis is a common disease in postmenopausal women. Several studies have analysed the associations between dietary supplementation with probiotics and bone health in postmenopausal women, but the results are still controversial. We conducted this meta-analysis to assess the effects of probiotics supplement on bone mineral density (BMD) and bone turnover markers for postmenopausal women.DesignSystematic review and meta-analysis.MethodsWe systematically searched PubMed, EMBASE and the Cochrane Library from their inception to November 2020 for randomised controlled trials (RCTs) assessing probiotic supplements and osteoporosis in postmenopausal women. Study-specific risk estimates were combined using random-effect models.ResultsFive RCTs (n=497) were included. Probiotic supplements were associated with a significantly higher BMD in the lumbar spine (standardised mean difference, SMD=0.27, 95% CI 0.09 to 0.44) than in control. There was no difference between probiotic supplements and BMD in hips (SMD=0.22, 95% CI −0.07 to 0.52). Collagen type 1 cross-linked C-telopeptide levels in the treatment groups were significantly lower than those of the placebo group (SMD=−0.34, 95% CI −0.60 to −0.09). In subgroup meta-analysis, levels of bone-specific alkaline phosphatase, osteoprotegerin, osteocalcin and tumour necrosis factor did not differ between the probiotic and placebo groups.ConclusionsWe conclude cautiously that supplementation with probiotics could increase lumbar BMD. More RCTs are recommended to validate or update these results.